A Case Handling Bladder Stone on The Turtle (Centrochelys sulcata) At The Griya Animal Lestari Clinic, Semarang - Rahman, Nurul Azizah Awaliyah; Musdalifah (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2024)
Turtles are reptiles that are very easy to recognize because they have a distinctive body shape. A distinctive characteristic of turtles is the presence of a shell called a carapace on the dorsal part and a plastron on the ventral part. Turtle Centrochelys In their habitat, turtles eat green vegetables. Green vegetables contain quite high levels of calcium oxalate which causes this bladder stone in the turtle's bladder C. sulcata. The purpose of this writing is to find out how to handle it bladder stone on the turtle C. sulcata.The treatment method is carried out by surgery using assistance Rochester carmalt hemostatic forceps through the turtle's cloaca to remove the calculi. The results obtained were that the calculi were successfully removed with the formation of oxalate crystals, the therapy given was neprolith medication. Conclusion the turtle experienced bladder stone, The calculi were successfully removed with treatment Rochester carmalt hemostatic forceps.